CO2 Addition and Semicontinuous Feed Regime in Shaded HRAP—Pathogen Removal Performance - Ruas, Graziele [UNESP]; Lacerda, Sarah Farias; Nantes, Maria Alice; Serejo, Mayara Leite; da Silva, Gustavo Henrique Ribeiro [UNESP]; Boncz, Marc Árpad (MDPI, 2022)
The influence of CO2 addition and feeding regime (continuous versus semicontinuous) on the removal of Pseudomonas aeruginosa, Clostridium perfringens, Staphylococcus, Enterococcus faecalis, and Escherichia coli (E. coli) from three shaded high-rate algal ponds (HRAPs) treating raw sewage (RS) was studied. The three HRAPs were operated at an analogous hydraulic retention time (HRT) for 5 days and with shading of 50%. The CO2 addition and feeding regime had no statistically significant influence on the removal of Pseudomonas aeruginosa, Clostridium perfringens, Staphylococcus sp., and Enterococcus faecalis, with 2.39–3.01, 2.07–2.31, 3.02–3.38, and 3.14–3.45 log units, respectively. However, the removal of E. coli decreased significantly with the feeding regime of 0.1 h d−1 and 2.23–3.29 log units. The productivity and the total suspended solids (TSS) removal efficiency were significantly improved with the semicontinuous feeding regime and CO2 addition. The highest productivity was obtained in the semicontinuous feeding regime, 5.93 g m2 d−1, while the TSS removal efficiency was similar between the semicontinuous feeding regime and CO2 addition (31–36%). The control of light intensity led to greater variability in the algal community, and was present in the three reactors, in different proportions, in the form of the microalgae Scenedesmus acutus, Scenedesmus obliquus, and Chlorella sp.
Keywords: Clostridium perfringens; disinfection; pathogenic indicator organisms; scrubbing; sewage; Staphylococcussp